Stature in Yogyakartas students and prehistoric Balinese circa 1100 A.C. - Etty Indriati, Etty Indriati (Universitas Gadjah Mada, 2002)
Background: Stature is one of growth and development indicators among others such as weight, dental eruption, and bone development. Stature varies between populations and races, and changes across times and spaces.Aim of study: to understand the average stature of groups of Indonesians relative to other populations worldwide; and to understand the anthropological category of Indonesians stature. Material and methods: Subjects were students of National University of Yogyakarta consisted of 245 people. Sex, age and their statures were recorded. In addition, the stature of 47 human skeletal remains from prehistoric Bali were measured utilizing regression formula of Mongolid race.Results: The average stature of Yogyakarta National University students in 1980s was 165 cm and 152.8 cm in males and females respectively. In the 1990s, their statures were 165.4 cm and 153.7 cm respectively. The prehistoric Balinese circa 1100 A.D. had statures of 164.4 cm and 157.3 cm in males and females respectively.Conclusion: Increased stature of 0.4 cm in males and 0.9 cm in females among Yogyakarta students in one decade might have been related to better nutrition, social and economy from the 80s to the 90s. Within two millennia, Indonesian stature has not undertook significance change. Indonesian stature is medium relative to other populations stature worldwide; and in the range of stature of people from China, Hongkong, Taiwan, Thailand, and India. However, Indonesian stature is below the average stature of European and American people. This suggests that race/genetics are more prominent as contributing factors reaching terminal stature, compared to latitude (weather and geograpy).Keywords: stature, Yogyakarta, Bali, anthropology, growth